Peningkatan Kondisi Fisik Atlet Melalui Interval Training dan Circuit Training - Hulfian, Lalu (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2016)
Exercise Â is Â physical Â activityÂ done Â by Â human Â to Â improve Â health Â and physical Â condition. Judging from its goal, sport is a skill that aims to gain achievement through athletic sports, games, martial arts etc. Thus, in each branch of the sport is required to have a prime physical condition. Judging from the characteristics of the sport, the much-needed physical condition is derived from anaerobic and aerobic, where anaerobic is emphasized in strength, especially leg muscle strength, whereas aerobics is emphasized on the immune system, especially maximal oxygen volume. To practice the anaerobic and aerobic exercise, it takes a training method One of the exercises used to improve both physical conditions is by the method of interval training and circuit training. Therefore, researchers wanted to know the effect of the Air Alert training program using interval training methods to increase leg muscle power and maximum aerobic capacity. The research method used in this study is the experimental method because it Â seeks Â aÂ causal Â relationship Â between Â two Â variables Â that Â is Â interval Â and Â circuit Â training methods to improve the physical condition of leg muscle power and maximal oxygen volume. The study was located in Mataram by taking samples of athletes aged 18-22 years, amounting to 30 people divided randomly into 2 groups, namely the first group for interval training treatment, and the second group for the treatment of circuit training. The test used was a vertical jump test using a DF jump to measure leg muscle power and a bleep test to measure maximum aerobic capacity. It is expected that the product will be created in the form of an exercise Â program Â with Â interval Â trainingÂ method Â with Â repetition Â and Â set Â that Â has Â been determined that can be used to increase leg muscle power and maximum aerobic kapaitas so it can improve the achievement.